(De)Constructing Ideas of Security: Discovering an Alternative to the European Union External Border Control - Muhammad Wijaya Nur Shiddiq (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
The 'immigration crisis' of 2015, as well as the increasing reluctance of European Union (EU) countries, such as Poland to accept asylum seekers, has been a prominent topic of discussion in recent years. Numerous migrants were compelled to undertake a perilous expedition and perish at the threshold of Europe in a bid to flee hazardous conflicts in their countries of origin. This issue has raised doubts about the EU's commitment to maintaining its foundational humanitarian principles, as outlined in Article 2 of the Treaty on European Union. By employing a qualitative research methodology and (Just) Securitisation Theory–which falls under the paradigm of social constructivism–as an analytical tool, the author focuses on the legal aspect and the practical methods safeguarding external borders of the EU, namely the European Union Naval Force Mediterranean (EUNAVFOR MED), as a response to the increase of migration. Given this basis, this study concurs that: 1) the EU strategy to migration management has not adopted a comprehensive security approach, which results in the neglection of the safety of asylum seekers; 2) EU law instruments regarding migration curtails the free movement of people, and thus is discriminatory towards asylum seekers; 3) EUNAVFOR MED is insufficient in ensuring the security of migrants, and yet its securitising moves are disproportionate to the threat in the region. Keywords: European Union, Border Control, Securitisation, Just Securitisation Theory, EUNAVFOR MED